13.1k views
8 votes
-4(x-4)=-44
Please answer this with how you got the answer.

User Tameeka
by
4.9k points

1 Answer

14 votes

Answer: x = -15

Explanation:

Think PEMDAS

First, we factor the parenthesis:

-4 (x-4) = -4(x) + -4(-4)

now we are left with -4x + 16 = -44

Next is to isolate the "x":

to do this, we must subtract 16 from -44

-44 - 16 = 60

now we have -4x = 60

Now we divide both sides by -4 in order to isolate "x"

dividing -4x/-4 = x

diving 60/-4 = -15

the answer is x= -15

User Vassi
by
5.6k points